Forensic fraud : evaluating law enforcement and forensic science cultures in the context of examiner misconduct - Turvey, Brent E. (Amsterdam : Elsevier, 2013)
Forensic Fraud is a timely work that examines the problem of forensic fraud both theoretically and empirically, assessing the relationships among examiner, workplace, evidentiary, and impact variables. Unvalidated or improper forensic science is a leading cause of wrongful convictions. In more than 50% of the DNA exonerations nationwide, unvalidated or improper forensic science contributed to the underlying wrongful conviction. These problems include forensic techniques that have not been subjected to rigorous scientific evaluation (such as hair microscopy, bite mark comparisons, firearm tool mark analysis and shoe print comparisons); testing that is improperly conducted or analysis that is not accurate (regardless of whether the forensic technique involved is validated); and forensic misconduct (such as fabricated test results and misleading testimony). Forensic Fraud is written by a forensic scientist for the forensic science community, rather than by legal scholars or practitioners, as has been the trend. Responds directly to the dramatic increase in forensic fraud related laboratory scandals and closures that have plagued the forensic science community. Offers realistic recommendations and reforms ideally suited for forensic science professionals, legal practitioners, laboratory supervisors, forensic science students and academicians.
Includes bibliographical references (pages 255-276) and index.
Includes bibliographical references and index.
Keywords: Fraud investigation -- United States; Criminal Investigation -- United States